Cong xiao re'ai kexue/Cong xiao duanlian shenti zhangda baowei zuguo
'Love science from an early age on/Train the body when small, to protect the mother country when grown up.' Fourth of partriotic/educational series for primary and middle schools. ISBN 7-03-001305-0/G.83. Four posters in one plastic bag.